Evaluation of the Impact of Credit Payment Relaxation Stimulus on Credit Management at BPR X - Laxmi Jullianeth; Fitriany Fitriany (Eduvest - Journal of Universal Studies, 2025)
This case study aims to evaluate the implementation of credit management policies, the impact of implementing credit management policies and the obstacles and problems faced by BPR X in implementing risk management policies, especially related to the Covid-19 stimulus in accordance with POJK No.48/POJK.03/2020. This study uses qualitative research methods through interviews and document analysis such as Bank Internal Policy Documents, annual reports, and financial statements. This research shows that although there are still some limitations, BPR X has implemented credit management principles that are in accordance with applicable regulations and have been included in the bank's internal policies. The implementation of these principles has had a positive impact on BPR X's financial performance during the pandemic. However, there are obstacles in the implementation of policies related to the Covid-19 stimulus, namely the mismatch between the established debtor criteria and the actual condition of the debtor during document validation. The study found that BPR X's NPL ratio increased significantly from 9.45% in 2021 to 20.35% in 2023, indicating challenges in credit quality management despite stimulus implementation.